2019
DOI: 10.21037/gs.2019.12.17
|View full text |Cite
|
Sign up to set email alerts
|

Simple prosthesis versus prosthesis plus titanium-coated polypropylene mesh for implant-based immediate breast reconstruction after total mastectomy for breast cancer

Abstract: Background: Our study compares the cosmetic effects, postoperative complications, and quality of life of immediate breast reconstruction with simple prosthesis or prosthesis plus titanium-coated polypropylene mesh (TCPM) after total mastectomy for breast cancer.Methods: In total, 69 patients who underwent total mastectomy, sentinel lymph node biopsy, and immediate prosthetic breast reconstruction from January 2015 to December 2018 in our hospital were selected, and their cosmetic effects, complications, and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…11,21 Of the seven studies, three were 3-arm studies, including two studies comparing TiLOOP bra versus ADM versus partially absorbable synthetic mesh, 21,24 and one study comparing TiLOOP bra versus ADM versus simple prosthesis. 6 However, only two studies in our analysis reported BREAST-Q scores, both with available Physical Well-Being scale of the BREAST-Q data. 11,22 The risk of bias assessment result was presented in Supplemental Table S2.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…11,21 Of the seven studies, three were 3-arm studies, including two studies comparing TiLOOP bra versus ADM versus partially absorbable synthetic mesh, 21,24 and one study comparing TiLOOP bra versus ADM versus simple prosthesis. 6 However, only two studies in our analysis reported BREAST-Q scores, both with available Physical Well-Being scale of the BREAST-Q data. 11,22 The risk of bias assessment result was presented in Supplemental Table S2.…”
Section: Resultsmentioning
confidence: 93%
“…A total of 182 publications were identified in the first search, of which seven studies met our inclusion criteria and were eligible for the present meta-analysis (Table 1). 6,11,[21][22][23][24][25] There was one prospective randomized controlled study, 23 the other six were retrospective studies. 6,11,21,22,24,25 Among these studies, there were four studies of one-stage reconstruction comparing the complication risk between TiLOOP bra and ADM, 6,22,23,25 the other three included both one and two-stage reconstruction.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations